2019
DOI: 10.3389/fvets.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Modifies the Transcriptional Pattern of the Endometrium and Advances Embryo Development in Pigs

Abstract: Results: Embryo viability was equal between the groups (∼93%), but embryo development was significantly (P < 0.05) more advanced in the SP-treated group compared to control. A total of 1,604 endometrium transcripts were differentially expressed in the SP group compared to the control group. An enrichment analysis showed an overrepresentation of genes and pathways associated with the immune response, cytokine signaling, cell cycle, cell adhesion, and hormone response, among others.Conclusions: SP infusions prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 88 publications
(87 reference statements)
2
32
0
Order By: Relevance
“…These findings suggest that application of SP in ET-protocols could increase ET-outcomes by increasing the number of embryos succeeding during the crucial implantation window. Such a statement is based on the confirmation of previous findings [18,19,21], indicating that the effects of SP remain influential over time. Particularly, SP infusions at estrus advance embryonic development, and alters the expression of the endometrial genes and pathways potentially involved in embryonic development and maternal immune system tolerance during early pregnancy [19].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…These findings suggest that application of SP in ET-protocols could increase ET-outcomes by increasing the number of embryos succeeding during the crucial implantation window. Such a statement is based on the confirmation of previous findings [18,19,21], indicating that the effects of SP remain influential over time. Particularly, SP infusions at estrus advance embryonic development, and alters the expression of the endometrial genes and pathways potentially involved in embryonic development and maternal immune system tolerance during early pregnancy [19].…”
Section: Discussionmentioning
confidence: 52%
“…In pigs, SP infusions during estrus influenced the uterine environment during at least the first nine days of pregnancy, with changes of specific endometrial cytokines known to promote embryo development and implantation [18]. Our own findings revealed that SP infusions during estrus not only advance embryo development in pigs, but also change the global endometrial transcriptome at Day 6 of pregnancy [19]. This particular study showed >1600 endometrial transcripts differentially expressed in SP-treated endometrium compared to controls, depicting overrepresentation of genes and pathways potentially involved in embryo development and implantation, such as immune response, cytokine signaling, cell cycle, cell adhesion and hormone response [19].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Nevertheless, several factors could be involved in this fact. First, it has been shown that seminal plasma proteins and other components activated changes in the gene expression of the endometrium [44,46,47]; but in our study, the level of seminal plasma in the insemination dose was low because the ejaculate was diluted in commercial extender, so its impact on the genomic expression of the endometrium could be limited. Second, although uterus is colonized by the sperm within minutes after deposition [48] the differences detected in gene expression were evaluated 24 h after semen deposition [43][44][45], while our measurements were carried out only 2 hours after insemination.…”
Section: Discussionmentioning
confidence: 67%
“…However, semen has, by its specific sperm-and SP constituents proven able to induce major changes in the expression of genes in tissues of the internal genital tract alongside fertilization, in animal classes as disparate as insects or pigs [9]. Such changes clearly indicate pathways governing sperm transport [10], ovulation [11], sperm storage [4,6,12], sperm capacitation [12,13] and gamete encounter [14], processes that apparently continue during early embryo development and-for Eutheria-with placental development and pregnancy [11,15]. To complicate matters, while fertilization can be achieved without the intervention of immune responses, immunity modulation is apparently crucial to tolerate the presence of a foreign cell (the spermatozoon) and the proteins it and the accompanying SP carries in a female whose innate and adaptative immune system is prompt in eliminating both pathogens and foreign antigens.…”
Section: Introductionmentioning
confidence: 99%